The Influence Of Hybrid Working Model On Employee Engagement Through Work-Life Balance On Millennial Generation Employees - Angga Dutahatmaja (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
The transformation of the post-COVID-19 work world has encouraged the implementation of a hybrid work model that combines on-site and remote work. However, its impact on work-life balance (WLB) and Employee Engagement (EE) in the millennial generation still varies, depending on job characteristics. This study aims to analyze the effect of the hybrid working model (HWM) on EE through WLB mediation, by comparing two groups of workers: office employees and sales-marketers. This study uses a quantitative approach with the Multiple Group Analysis (MGA) method through SmartPLS. The sample consisted of 140 respondents who were evenly divided into 70 office employees and 70 sales-marketers in Surabaya, selected using a purposive-random volunteer sampling technique. Data were analyzed descriptively and inferentially to test the causal relationship between variables. The results showed that HWM had a significant positive effect on WLB for office employees, but was not significant for sales-marketers. Meanwhile, HWM had an insignificant negative effect on EE for office employees, but was significantly positive for sales-marketers. WLB was shown to increase EE in both groups. WLB mediation also strengthens the influence of HWM on EE. This finding highlights the importance of adjusting HWM policies based on job type to improve employee well-being and engagement.